Pierce Butler papers - Butler, Pierce, 1744-1822.
Notes of proceedings of the Constitutional Convention containing notes of remarks by Oliver Ellsworth, Benjamin Franklin, Elbridge Gerry, Alexander Hamilton, John Lansing, James Madison, William Paterson, Charles Pinckney, Charles Cotesworth Pinckney, Edmund Randolph, John Rutledge, Roger Sherman, Hugh Williamson, and James Wilson; with printed drafts of the Constitution, notes, resolutions, and other material. Also, letter (1779 May) from Butler to Benjamin Lincoln.
In part, positive photocopies.
U.S. senator from South Carolina, state legislator, and public official.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Ellsworth, Oliver, -- 1745-1807.; Franklin, Benjamin, -- 1706-1790.; Gerry, Elbridge, -- 1744-1814.; Hamilton, Alexander, -- 1757-1804.; Lansing, John, -- 1754-1829.; Lincoln, Benjamin, -- 1733-1810 -- Correspondence; Madison, James, -- 1751-1836.; Paterson, William, -- 1745-1806.; Pinckney, Charles, -- 1757-1824.; Pinckney, Charles Cotesworth, -- 1746-1825.; Randolph, Edmund, -- 1753-1813.; Rutledge, John, -- 1739-1800.; Sherman, Roger, -- 1721-1793.; Williamson, Hugh, -- 1735-1819.; Wilson, James, -- 1742-1798.; United States; United States. -- Constitutional Convention -- (1787)